Age-related gut microbiota succession in Neijiang pigs: insights for precision feeding and productivity - Wu, Qihang; Hu, Shijie; Wang, Yan; Wu, Yuanyuan; Zhao, Ye; Niu, Lili; Zhou, Xiaofeng; Shen, Linyuan; Liu, Yihui; Chen, Ying; Gan, Mailin; Zhu, Li (Frontiers in Microbiology, 2025)
ObjectiveTo characterize age-related gut microbiota succession in Neijiang pigs and translate these dynamics into actionable insights for precision feeding and productivity improvement.MethodsGrowth data from 0 to 180 days (n = 16, 780 weight records) were fitted with three non-linear models to determine the optimal growth curve and partition physiological stages. Fresh feces were collected at 25, 70, 110, and 150 days (n = 6/stage). 16S rRNA V3–V4 amplicon sequencing was used to profile microbiota composition and diversity; PICRUSt2 was employed to predict metagenome functions against the KEGG database.ResultsThe Gompertz model best described growth (R2 = 0.996) with an inflection point at 84.2 days (25.9 kg). Microbial alpha-diversity (Shannon, Chao1) increased with age and plateaued after 110 days. Firmicutes and Bacteroidota dominated (>90% relative abundance), whereas Spirochaetota and Euryarchaeota expanded significantly in finishing pigs. LEfSe identified 45 stage-specific biomarkers: Prevotella_9, Collinsella and Blautia characterized suckling–weaning stages; Faecalibacterium and Clostridium_sensu_stricto_1 peaked at 70 days; Lactobacillus was dominant at 110 days; Treponema, Streptococcus and Bacteroides defined the 150-day microbiome. Functional prediction revealed a metabolic shift from basal biosynthesis and DNA repair in early life toward enhanced ABC transporters, bacterial motility proteins, oxidative phosphorylation and methane metabolism in finishing pigs.ConclusionOur data provide a temporal blueprint of gut microbiota maturation that mirrors host nutrient requirements across growth phases. These microbial indicators and functional signatures can guide stage-specific dietary formulations and microbiota-targeted interventions to improve feed efficiency, reduce environmental emissions and enhance the productivity of indigenous pig breeds.